Study of forbidden transitions in atomic systems - Amaro, Pedro Manuel Duarte Gonçalves (2012)
A Thesis submitted for the co-tutelle degree of Doctor in Physics at Universidade Nova de Lisboa and Université Pierre et Marie Curie